Population pharmacokinetic/pharmacodynamic analysis of AK111, an IL-17A monoclonal antibody, in subjects with moderate-to-severe plaque psoriasis - Li, Qian; Qiao, Ju; Jin, Hongzhong; Chen, Benchao; He, Zhimei; Wang, Guoqin; Ni, Xiang; Wang, Max; Xia, Michelle; Li, Baiyong; Chen, Rui; Hu, Pei (Frontiers in Pharmacology, 2022)
AK111 is an innovative IL-17A antibody, presenting high affinity to IL-17A and showing similar pharmacokinetic (PK) characteristics to those of typical immunoglobulin (Ig) G1 antibodies. To optimize the dosage regimen for phase 2/3 clinical trials, PK and pharmacodynamics (PD) of AK111 were firstly characterized in Chinese moderate-to-severe plaque psoriasis patients in a phase 1b study. AK111 PK serum sample and Psoriasis Area and Severity Index (PASI) score data were collected from 48 moderate-to-severe psoriasis patients in this study. Non-linear mixed effects modeling was used for population PK/PD analysis. A one-compartment model with a first order absorption and a first order elimination best described the PK behavior of AK111. Apparent systemic clearance was 0.182 L/day and central volume was 6.65 L. The exposure–response relationship was characterized using an indirect response model. The pharmacological effect of AK111 was described in the form of inhibiting the formation of psoriatic plaque, whereas placebo was quantified in the form of promoting the degradation of psoriatic skin lesions. The maximum effect of drug effect (Imax) and placebo effect (PLBmax) was 1 and 0.429 respectively. The rate constant for psoriatic plaque production (Kin) was 0.474 PASI/day and psoriatic plaque loss (Kout) was 0.024 day-1. Body surface area (BSA) affected by psoriasis was identified as a significant covariate on K_out. Simulation results confirmed that all of predicted PASI90 response rates at week12 were higher than 60% at 150mg and 300mg dose levels with different regimens, and could reach higher than 80% at week 24. We hope this first PK/PD study of AK111 in Chinese moderate-to-severe plaque psoriasis patients will be of help in the further clinical development of AK111 and provide a reference to the dosage optimization for similar antibodies with a long half-life.